A conceptual model for advanced/metastatic gastric or gastroesophageal junction cancer: a review of qualitative studies and results from patient interviews - France Ginchereau Sowell; Thom de Milliano; Keri J. S. Brady; Ginamarie Foglia; Medha Sasane; Samira Bensfia; Matthew Reaney (BMC Cancer)
Abstract Background Despite approvals of new first-line immunotherapies for advanced/metastatic gastric cancer/gastroesophageal junction cancer (aGC/GEJC), patients’ median survival is around 14 months and their health-related quality of life (HRQoL) is affected by disease-related symptoms and treatment-related side effects. Using a targeted literature review (TLR) and patient interviews, this study identified disease- and treatment-related concepts that are important to patients with aGC/GEJC and their HRQoL. Methods A TLR was conducted to identify primary qualitative studies from 2018 to 2021 on patients’ experiences with aGC/GEJC. The results, supplemented with the results of two previously identified studies from 2017, were used to develop a preliminary conceptual disease model of aGC/GEJC and an interview guide. Next, one-to-one concept elicitation interviews were conducted where patients with aGC/GEJC were asked about symptoms, impacts on daily life, experience of care, treatment expectations, and clinical trials. The conceptual model was refined using these patient experience data. Results Four studies selected from the TLR and the two previously summarized studies identified 47 symptoms (15 disease-related, 20 treatment-related, 12 disease- and treatment-related) and 35 impacts. Interviews with 20 patients identified 36 symptoms. The 12 most important symptoms (mentioned by ≥ 50% of patients; average disturbance ratings: ≥5, scale: 0 'not disturbing' to 10 'extremely disturbing') were: nausea, fatigue, temperature sensitivity, indigestion, weakness, diarrhea, vomiting, early satiety, swallowing difficulties, taste alterations, abdominal pain, general pain. Symptoms were mostly attributed to systemic treatments (chemotherapy, immunotherapy and targeted therapy), followed by surgery. Thirty-one impacts emerged from the interviews, the most common being emotional disturbances, impacts on daily activities and families, and requiring assistance from caregivers. Patients were mostly positive about their experience of care, willing to enroll in clinical trials, and keen to receive innovative treatments with few side effects. The final conceptual disease model details the symptoms and impacts of aGC/GEJC. Conclusions The conceptual model provides valuable data on signs/symptoms and impacts of aGC/GEJC affecting patients’ lives. This can guide the clinical outcome assessment strategy for the development of innovative treatments more comprehensively than input from physicians alone, to ensure treatments improve both patients’ survival and HRQoL. Interviews also help understand patients’ perspectives on clinical trials.